The Role of Trust in Savings Decision Making - Setiawan, Barick Ahmad; Dharmawan, Donny; Dewi, Luh Komang Candra; Alimin, Erina; Setianti, Yanti (Yayasan Riset dan Pengembangan Intelektual, 2024)
The purpose of this research is to test the influence of religiosity, motivation, promotion on the decision to buy savings with trust as a mediating variable at Bank Sharia Indonesia Semarang. The research method is a quantitative method. The sampling technique uses accidental sampling so that 97 respondents are obtained. The data were analyzed using path analysis. The results of the research are that partial religiosity, motivation, promotion and trust have a significant effect on the decision to buy savings at Bank Sharia Indonesia Semarang. Trust is able to mediate the influence of religiosity, motivation, promotion on the decision to buy savings at Bank Sharia Indonesia Semarang. If customer trust in Bank Sharia Indonesia Semarang increases, customers will not turn to other sharia banks and will continue to use the services provided by Bank Sharia Indonesia Semarang.